IMPLEMENTASI MODEL PEMBELAJARAN PROJECT BASED LEARNING UNTUK MENINGKATKAN KEMAMPUAN NUMERASI - Sofia Ari (Lembaga PKBM Tunas Harapan Varoso, 2024)
This research aims to explain how to improve students' literacy and numeracy skills through the project based learning model. Literacy and numeracy skills are currently very much needed by students, especially in the independent learning curriculum, the national exam has been abolished and replaced with a minimum competency assessment or AKM. AKM was implemented after the literacy and numeracy results of Indonesian students were at a low level based on the PISA results in 2018. In AKM, students' abilities were tested, namely literacy and numeracy. Literacy and numeracy skills are very important for students to have. These abilities are closely related to understanding mathematical concepts and other concepts in everyday life. Literacy and numeracy skills are improved through project learning. In projects students are directly involved in making something and analyzing something with material. This research shows that the project bassed learning model can improve students' literacy and numeracy skills. This can be seen from the first cycle literacy and numeracy learning results of 55% and the second cycle literacy and numeracy learning results of 83%.